Halal Fashion Purchase Intention Through Tokopedia: A Dual-Model Perspective - Najmudin; Syihabudin; Ma’zumi; Isti Nuzulul Atiah; Suja’i; Sahraman D. Hadji Latif (Journal of Islamic Economics and Finance Studies, 2025)
The increase in the Muslim population, especially among the younger generation, has driven a global increase in halal fashion products. In Indonesia, fashion products have become the most popular category in e-commerce, in line with the growing awareness of religion and increasing digital penetration. Tokopedia, one of the biggest e-commerce platforms in the country, has become a promising channel for distributing halal fashion products. However, studies pertaining to the purchase intention of these products via online are still limited. This research establishes the impact of the Theory of Consumption Values (TCV) and Technology Acceptance Model (TAM) on attitudes toward halal fashion products and their impact on the purchase intentions of Muslim Generation Z (Gen Z) through the Tokopedia app. This research employs a quantitative approach comprising 266 Gen Z respondents from various provinces in Indonesia. Data collection was conducted through an online questionnaire, and the analysis was performed utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM). The results demonstrated that Functional Value (FV), Social Value (SV), and Emotional Value (EV) in TCV possess a substantial influence on attitudes toward halal fashion products. However, Epistemic Value (EPV) and Conditional Value (CV) show no significant effect. Meanwhile, in TAM, Perceived Ease of Use (PEOU) and Perceived Usefulness (PU) do not influence attitudes. Positive attitudes toward halal fashion products have been observed to play a substantial influence on Gen Z's intention to purchase halal fashion products through the Tokopedia App. Therefore, halal fashion practitioners need to highlight quality, comfort, inclusivity, attractive designs, and clear benefits on digital platforms. The government must also strengthen halal education, provide a trusted marketplace, and support Halal Fashion Micro, Small Medium Enterprise (MSMEs) and exports to advance the industry.   Pertumbuhan populasi Muslim, khususnya dari kalangan generasi muda, mendorong peningkatan permintaan global terhadap produk fesyen halal. Di Indonesia, produk ini menjadi kategori terlaris di e-commerce, seiring meningkatnya kesadaran religius dan penetrasi digital. Tokopedia, sebagai salah satu platform e-commerce terbesar di Indonesia, menjadi saluran potensial untuk distribusi produk fesyen halal. Namun, kajian mengenai niat beli produk ini secara online masih terbatas. Penelitian ini bertujuan untuk menganalisis pengaruh Theory of Consumption Values (TCV) dan Technology Acceptance Model (TAM) terhadap sikap pada produk fesyen halal dan dampaknya terhadap intensi beli Generasi Z (Gen Z) Muslim melalui aplikasi Tokopedia. Penelitian ini menggunakan pendekatan kuantitatif dengan melibatkan 266 responden Gen Z dari berbagai provinsi di Indonesia. Data dikumpulkan melalui penyebaran kuesioner online, dan dianalisis menggunakan Structural Equation Modeling (SEM). Temuan penelitian menunjukkan bahwa nilai fungsional, sosial, dan emosional dalam TCV berpengaruh signifikan terhadap sikap pada produk fesyen halal, sedangkan nilai epistemik dan kondisional tidak berpengaruh. Sementara itu, dalam TAM, persepsi kemudahan dan kegunaan tidak berpengaruh terhadap sikap. Sikap positif terhadap produk fesyen halal terbukti berpengaruh signifikan terhadap intensi Gen Z untuk membeli produk fesyen halal melalui Tokopedia. Dengan demikian, Praktisi fesyen halal perlu menonjolkan kualitas, kenyamanan, inklusivitas, desain menarik, dan manfaat jelas di platform digital. Dan, pemerintah harus memperkuat edukasi halal, menyediakan marketplace tepercaya, serta memberi dukungan pada UMKM dan ekspor fesyen halal untuk memajukan industri ini.